Ab Initio Study of the Raman Spectra of Amorphous Oxides: Insights into the Boson Peak Nature in Glassy TeO2. Issue 4 (21st February 2023) - Roginskii, Evgenii M.; Raghvender, Raghvender; Noguera, Olivier; Thomas, Philippe; Masson, Olivier; Bouzid, Assil
Abstract : Herein, a computational technique that combines density functional theory and the finite difference method is presented to enable the calculation of the Raman spectra of large models of oxide glasses. The calculated Raman spectra of amorphous TeO 2 are found to be in excellent agreement with the experimental data. A strong peak in the low‐frequency range of the Raman spectra is observed and attributed to the Boson peak. According to atomic‐scale analysis, this peak is assigned to collective vibrations of nanoclusters that are formed by the structural units of the glass. Two general factors that influence the Boson peak intensity are established. The first factor concerns the intensity of the low‐frequency peak in TeO 2 vibrational density of states. The second factor is related to the low‐frequency vibrational state occupancy at fixed temperature, which obeys the Bose–Einstein statistic. It is found that even a small shift toward high frequencies leads to a significant decay of the vibrational state occupancy. This correlates quite well when the Raman spectra of TeO 2 glass are compared to the spectra of fused silica. The technique can be readily applied to the large set of amorphous systems. Abstract : Raman spectra calculations are performed on large atomistic glassy oxide models by resorting to density functional perturbation theory and finite differences method. The analysis of the normal modes reveals that the Boson peak is due to collective vibrations of glassy structural units and that its intensity depends on the amplification of the lowest frequency modes.